Pemberdayaan ekonomi masyarakat melalui pemasaran digital pupuk abu hasil pengelolaan sampah di Kelurahan Babakan - Sri Jaya Lesmana; Hudaya Hudaya Latuconsina; Inas Sofia Latif; Aqilah Aulia Yumna; Cindy Aulia Herawati (Riau Journal of Empowerment, 2026)
Effective waste management is not only important for protecting the environment, but also has great potential as a sustainable economic solution. In Babakan Village, waste processed through the incineration process with REST-I becomes ash fertilizer so that it has economic value that contributes to waste reduction. The main challenge in the use of ash fertilizer is marketing that is still limited to the local scope. This Community Service (PKM) activity aims to empower the community through digital marketing as a strategic step in creating sustainable economic solutions. Through digital marketing training and assistance, the public is invited to take advantage of digital technology such as social media and marketplaces to expand the reach of product marketing. Thus, ash fertilizer products can not only be accessed by the local market, but also reach consumers in various regions and can increase the income of the local community. PKM activities also focus on developing environmental awareness and community-based economic empowerment, with the aim of realizing an environmentally friendly and sustainable economy.